Analysis of the Social Role of Educators in the Formation of Students' Learning Interests at UPT SPF SDN Kalukuang IV, Tallo District Makassar City - M, Asrianti; Hanafi, Ali; Iskandar, Abd. Malik (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2024)
Student learning interest is a key factor in the success of the educational process. The social role of educators has a significant contribution in shaping learning interest through interaction and personal approach. This study aims to analyze how the social role of educators influences the formation of student learning interest at UPT SPF SDN Kalukuang IV, Tallo District, Makassar City. This study uses a descriptive analysis research type with a qualitative approach. Data were obtained through in-depth interviews, participatory observation, and document analysis. The results of the study indicate that educators not only act as teachers, but also as motivators, facilitators, and social guides who are able to create a conducive learning environment. Factors such as interpersonal communication, understanding student needs, and the ability to build positive relationships are key to increasing learning interest. The main challenge faced is the limited facilities and infrastructure, but this can be overcome with innovation in creativity-based learning approaches. This study is expected to be a reference for educators and policy makers in optimizing the social role of educators to increase student learning interest.